Promoting innovative experiential learning practices to improve academic performance: Empirical evidence from a Spanish Business School - Antonio L. Leal-Rodríguez; Gema Albort-Morant (Journal of Innovation & Knowledge (JIK), 2019)
There are plenty of theoretical studies addressing how active-based practices and methodologies influence university students' level of performance. However, there is a scarcity of works that bring empirical evidence to sustain the existence of a positive link between the students' involvement in experience-based learning methods and their academic results. The aim of this paper is to examine the impact exerted by an experiential learning based educational methodology on students' level of academic performance. This research was carried out within the specific context of a Spanish private business school, using a sample of students belonging to the Bachelor's Degree in Business Administration at a Spanish Business School. Pearson's correlation and structural equation modeling are applied to test the relationship hypothesized. Our results derived from the analysis of an undergraduate business students sample suggest that getting involved in experience-based practices and managerial simulations constitutes an effective approach to develop their competencies. Thus, we may conclude that fostering experiential learning strategies favors the students' understanding of theoretical concepts and leads to the attainment of superior performance. This paper contributes to management education by empirically testing the value of innovative experiential learning based training.
Keywords: I23; A22; 650; Academic performance; Experiential learning; Innovative learning practices; Management education